DETERMINATION OF THE INITIAL CONDITIONS OF ROAD TRAFFIC ACCIDENTS IN THEIR CONSEQUENCES - E. K. Agakhanov; E. Z. Batmanov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Developed a calculation-experimental method of determining the initial conditions of road traffic accidents in their consequences in the event of a frontal collision.